DETERMINATION OF PRIORITY QUALITATIVE FACTORS OF STIMULATION OF THE WORK OF ENTERPRISE TOP MANAGERS - Malyarets, Lyudmula; Iastremska, Olena; Tutova, Anastasiia (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2022)
The article is devoted to substantiation of the main subjective qualitative factors which are typical for labor incentives of managers of the strategic level of enterprises management, and which it is reasonable to take into account while developing the system of economic incentives of their activity, since basing and determination of the incentives amount only on the statistical objective information is not able to influence significantly the final results of top-managers work. The purpose of the article is to identify priority qualitative factors of influence on the process of economic stimulation of the activity of top managers of industrial enterprises and their quantitative interpretation based on the combination of qualitative assessments into an integral indicator. The tasks of the article are the analysis of the results of the survey of top managers on individual qualitative factors of influence on their motivation, the definition of statistical relationships between factors, determining the explicit and latent trends in the dynamics of these factors, the calculation of the integral indicator of the impact of the identified significant factors, the formation of methodological support to identify priority qualitative factors of economic incentives performance of top managers of industrial enterprises. The object of the article is the process of economic stimulation of the results of activity of top managers of industrial enterprises. The subject of the article is the theoretical provisions, methodological support, and practical proposals for economic incentives for managers of the strategic level of administration at industrial enterprises. Methods. To achieve the goal, the article used the following basic general and special research methods: theoretical generalization, questionnaire survey, descriptive statistics tools, Spearman rank correlation coefficient, multivariate factor analysis, method for calculating the integral index of qualitative factors of managers’ labor stimulation, graphical method. Results. The results of the study are: the scientific achievements of the predecessors on the formation and use of performance indicators of enterprises as indicators of incentives for top managers; surveyed top managers of industrial enterprises regarding their opinions on the main factors influencing the performance of their own activities; proved the relationship of influence factors on the incentives of top managers presented in the questionnaire; clear and latent tendencies of interrelation of factors of influence on productivity of managers of strategic level of the enterprises are revealed; the integrated indicator of qualitative factors of stimulation of work of managers is defined, quantitative values of which have proved existence of insufficient account of factors on process of stimulation. Conclusions. As a result of determining the relationship between the qualitative factors influencing the economic incentives of top managers developed methodological support, which differs: the content of qualitative factors; analysis of the structure of the studied set of arrangements of answers of experts using the tools of descriptive statistics; assessment of the closeness of the relationship between qualitative factors of economic incentives for top managers in the dynamics; assessment of the consistency of the answers of experts in the dynamics; identification of latent factors of economic stimulation of top managers; analytical method of developing an integrated quality indicator of economic stimulation for top managers.